The indiscriminate use of Ritalin to improve academic performance (Research, Society and Development, 2021)
Ritalin, as it is more commercially known, is one of the main drugs that stimulate the central nervous system, is the most consumed psychostimulant in the world and its main through the literature of articles the issue of use for cognitive improvement and even recreational. Where it will also address its mechanism of action, ADHD, adverse effects and possible interactions that the drug can cause. This paper proposes to analyze how drug misuse can bring benefits and harm to the user´s health, especially mental health, which is the most affected, promising hours of study and prolonged concentration, which misuse can bring benefits and harm to the user´s health, especially mental health. which is the most affected, promising hours of study and prolonged concentration, wich is why it is known as the “intelligence drug”.